The type of food influences the behaviour of Listeria monocytogenes in a food-gastrointestinal-infection model - Nadja Pracser; Andreas Zaiser; Luminita Ciolacu; Franz-Ferdinand Roch; Narciso M. Quijada; Sarah Thalguter; Monika Dzieciol; Beate Conrady; Martin Wagner; Kathrin Rychli (npj Science of Food)
Abstract Food contaminated with Listeria (L.) monocytogenes is the main source of human listeriosis, but how different food matrices affect the survival and invasion in the gastrointestinal (GI) tract is still unclear. This study examined three ready-to-eat foods - soft-cheese, smoked salmon, and sausage - using a food-GI-infection model. We observed strain-dependent growth rates, but food matrices did not significantly impact growth. However, nutrient sources altered gene expression. Passage through the GI model upregulated 23 stress genes and 29 virulence genes (e.g., clpE, hly, and plcB). L. monocytogenes survival was higher in cheese and fish compared to sausage, due to their lower buffer capacity. Invasion efficiency into Caco-2 cells was highest in fish, potentially linked to its fatty acid composition. Food matrices and GI conditions influenced the transcriptional profiles of stress-associated and virulence genes. This study highlights the significant role of food matrices in L. monocytogenes survival and infection.